Kesaputta Sutta: Philosophy regarding the path to the end of life’s pursuits - Phrakhrupalat Winai Thirapunyo (Noi Chomphu) (Journal of Contemporary Buddhist Society = JCBS, 2022)
This academic article aims to study "The Ultimate Seek" for Truth in Philosophy According to the study, it was found that there are 2 major ways of seeking truth in philosophy as follows: (1) Sensory or experiential pursuit of truth which philosophy is called inductive truth-seeking which is a way of acquiring materialistic knowledge.(2) the ultimate pursuit of rational truth which philosophy is called Deductive truth-seeking is a method of seeking truth among idealists. The ultimate philosophical pursuit of truth that appears in the Kesputta Sutta (Kalama Sutra) is the pursuit of the Ten Truths. After that, use careful judgrnent and then believe in the ultimate process of seeking truth in philosophy as shown in the Kesputta Sutta. There are 2 processes. (1) The process of seeking truth based on experience, ile. the philosophical use of internal and external consciousness is called inductive pursuit of truth In the Kesputta Sutra, verses 1-4 and (2) The pursuit of truth based on reason, which is philosophically called The deductive form of idealism in the Kesputa Sutra is verses 5-10, the ultimate part of seeking truth in the Kesputa Sutra. It is the use of both the methods of induction, namely the paratoghosha, and the abbreviated, that is, the use of yoniso manasikara, after carefull consideration and then believing.